2012
DOI: 10.1074/jbc.m112.370403
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Events Initiating Exit of a Copper-transporting ATPase ATP7B from the Trans-Golgi Network

Abstract: Background: ATP7B trafficking from Golgi to vesicles is essential for copper homeostasis. Results: Mutating Ser-340/341 alters the inter-domain contacts, diminishes protein phosphorylation, and shifts ATP7B localization to vesicles. Conclusion: Spatial arrangement of functional domains determines ATP7B readiness to traffic, whereas phosphorylation may maintain the trafficking-compatible state. Significance: The proposed mechanism explains how unrelated signals trigger similar trafficking responses from ATP7B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
73
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 34 publications
1
73
0
Order By: Relevance
“…Thus, our studies reached the unexpected conclusion that the competence of all six MBDs to bind copper was not required to observe copper-dependent apical targeting, suggesting the existence of another copper-sensing domain(s) in ATP7B (39,40) that regulates the apical targeting step in polarized cells. Our studies extend previous ones that have suggested that copper binding to MBDs triggers conformational changes that propagate structural changes to other domains of ATP7B and trigger its TGN exit via vesicles (13). We suggest an additional role for copper-stimulated conformational changes: perhaps those structural changes expose both the apical targeting motif and C-terminal Ser/Thr to TGN-resident kinases in a copperdependent manner.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…Thus, our studies reached the unexpected conclusion that the competence of all six MBDs to bind copper was not required to observe copper-dependent apical targeting, suggesting the existence of another copper-sensing domain(s) in ATP7B (39,40) that regulates the apical targeting step in polarized cells. Our studies extend previous ones that have suggested that copper binding to MBDs triggers conformational changes that propagate structural changes to other domains of ATP7B and trigger its TGN exit via vesicles (13). We suggest an additional role for copper-stimulated conformational changes: perhaps those structural changes expose both the apical targeting motif and C-terminal Ser/Thr to TGN-resident kinases in a copperdependent manner.…”
Section: Discussionsupporting
confidence: 66%
“…they all showed increased ATP7B in vesicles. The conclusion of this study was that phosphorylation does not initiate ATP7B trafficking per se but rather maintains the protein in a trafficking-permissive state following a copper-induced conformational change (13). Overall, the relationship between copper-stimulated Ser/ Thr hyperphosphorylation and copper-dependent trafficking remains enigmatic, and the ATP7B residues phosphorylated physiologically in high copper remain undetermined.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…In addition to the cellular components required for copperdependent ATP7B trafficking, studies have shown that molecular signals within the protein, as well as intramolecular interactions, play important roles (30,40). Two well-characterized trafficking signals encoded within the primary sequences of both copper-ATPases have been identified: (i) F 37 -E 45 in ATP7B, which is required for retention of ATP7B in the TGN (−Cu) and targeting to the apical region in polarized hepatic cells (+Cu, anterograde trafficking) (11); and (ii) di-and trileucines in ATP7A and ATP7B's C-termini, which are needed for retrograde trafficking to the TGN (−Cu) (12,41,42).…”
Section: Discussionmentioning
confidence: 99%